2022
DOI: 10.1177/21582440221079887
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model for the Antecedents and Consequences of Internal Crisis Communication (ICC) in Malaysia Oil and Gas High Risk Industry

Abstract: A considerable amount of literature has concluded that employee relations has always been overlooked in the area of crisis communication. Therefore, the aim of this study is to investigate the antecedents of internal crisis communication (ICC) that include safety culture, supportive environment, social media usage, management commitment and the consequences on the other hand comprising affective commitment, perceived organizational support, and employee crisis perception in the context of high risk industry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 124 publications
(178 reference statements)
3
9
0
1
Order By: Relevance
“…Accordingly, effective internal communication during a crisis is believed to provide a supportive environment that makes the employee work comfortably without the fear of unknown. This finding corroborates with the study of Mohamad et al. (2022)…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, effective internal communication during a crisis is believed to provide a supportive environment that makes the employee work comfortably without the fear of unknown. This finding corroborates with the study of Mohamad et al. (2022)…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, effective internal communication during a crisis is believed to provide a supportive environment that makes the employee work comfortably without the fear of unknown. This finding corroborates with the study of Mohamad et al (2022) Also, the data gathered indicated that ICC deployed by an organisation positively affects employees feeling of insecurity triggered by the crisis. This hypothesis suggests that employees are more interested in knowing the organisational situation regarding job continuity and financial survival.…”
Section: Discussionsupporting
confidence: 91%
“…The reliability of the instruments was also evaluated using Cronbach's alpha as it is the most common and widely known method. As a rule of thumb, a measurement construct is deemed reliable with its scale demonstrating high alpha scores greater than 0.70 (Schjoedt et al , 2014; Mohamad et al , 2022). In this study, the Cronbach's alpha values for each construct ranged from = 0.704 to = 0.911, which are in line with the recommended value.…”
Section: Results and Analysismentioning
confidence: 99%
“…Hal ini terlihat dari hasil penelitian. Terbukti bahwa pada saat pembuatan sertifikat insentif sosial, format sertifikat tidak sesuai dengan apa yang diminta oleh departemen lain dan tidak ada pemberitahuan terlebih dahulu mengenai perubahan format tersebut, sehingga mengakibatkan tidak terselesaikannya kewajiban yang telah diajukan sesuai dengan yang diimpikan oleh pimpinan dan departemen lain (Mohamad et al, 2022;Okaie, 2021;Suriyana, 2021).…”
Section: Metode Penelitianunclassified